Estimation of fluoride concentration in drinking water and common beverages in United Arab Emirates (UAE) - Tarun Walia; Salem Abu Fanas; Madiha Akbar; Jamal Eddin; Mohamad Adnan (Saudi Dental Journal)
Objective: To assess fluoride concentration in drinking water which include tap water of 4 emirates - Abu Dhabi, Dubai, Sharjah and Ajman plus bottled water, commonly available soft drinks & juices in United Arab Emirates. Methods: Five different samples of tap water collected from each of the four emirates of UAE: Ajman, Sharjah, Abu Dhabi and Dubai; twenty-two brands of bottled water and fifteen brands of popular cold beverages, purchased from different supermarkets in U.A.E were tested using ion selective electrode method and the fluoride concentration was determined. Results: The mean fluoride content of tap water samples was 0.14 mg F/L with a range of 0.04–0.3 mg F/L; with Ajman tap water samples showing the highest mean fluoride content of 0.3 mg F/L. The mean fluoride content for both bottled drinking water and beverages was 0.07 mg F/L with a range of 0.02–0.50 mg F/L and 0.04–0.1 mg F/L respectively. Majority (68.2%) of the bottled water are produced locally within U.A.E while a few (31.8%) are imported. Conclusions: The tap water, bottled water and beverages available in U.A.E show varying concentrations of fluoride, however none showed the optimal level necessary to prevent dental caries. Dental professionals in U.A.E should be aware of the fluoride concentrations before prescribing fluoride supplements to children. Keywords: Beverages, Drinking water, Fluoride, United Arab Emirates